Body size and body composition: a comparison of children in India and the UK through infancy and early childhood. Issue 12 (16th July 2015) - D'Angelo, S; Yajnik, C S; Kumaran, K; Joglekar, C; Lubree, H; Crozier, S R; Godfrey, K M; Robinson, S M; Fall, C H D; Inskip, H M
Abstract : Background: Indian babies are characterised by the 'thin-fat phenotype' which comprises a 'muscle-thin but adipose' body composition compared with European babies. This body phenotype is of concern because it is associated with an increased risk of diabetes and cardiovascular disease. We examined whether the 'thin-fat phenotype' persists through early childhood, comparing Indian children with white Caucasians in the UK at birth, infancy and childhood, using comparable measurement protocols. Methods: We used data from two cohorts, the Pune Maternal Nutrition Study (N=631) and the Southampton Women's Survey (N=2643). Measurements of weight, head circumference, mid-upper arm circumference, height, triceps and subscapular skinfold thickness were compared at birth, 1, 2, 3 and 6 years of age. SD scores were generated for the Pune children, using the Southampton children as a reference. Generalised estimating equations were used to examine the changes in SD scores across the children's ages. Results: The Indian children were smaller at birth in all body measurements than the Southampton children and became relatively even smaller from birth to 2 years, before 'catching up' to some extent at 3 years, and more so by 6 years. The deficit for both skinfolds was markedly less than for other measurements at all ages; triceps skinfold showed the least difference between the two cohorts at birth, and subscapular skinfold at all ages after birth. Conclusions: The 'thin-fat phenotype' previously found in Indian newborns, remains through infancy and early childhood. Despite being shorter and lighter than UK children, Indian children are relatively adipose.